Characterization Of Spatial Variability Of Soil Engineering Properties At USM Engineering Campus - Ling, Chee Kiong (Universiti Sains Malaysia, 2006)
Studies on the spatial variability of soil engineering properties are limited in the south-east Asia. Understanding the variability of soil properties is significant to land management practices including planning and adopting conservation works for soil erosion, slope stability, landslide control and soil hydrological response modeling. This study examines the spatial variability of soil engineering properties (moisture content, bulk density, particle size distribution, organic content and specific gravity) in a flat region under tropical climate using geostatistical and statistical methods. Soil samples were taken from a 137 ha area of the Universiti Sains Malaysia. The study area was divided into a number of geo-grid reference points and soil samples were collected at grid intersection points. The Global Positioning System (GPS) was used for locating the sample position. Large spatial variability of soil fines content and moisture content were found to exist in the study area and the degree of variability was heterogeneous among different soil properties. About 74–84% of the observed total variability in soil properties was due to spatial structure. All the soil properties tested, exhibited strong spatial dependency and were spatial dependent up to distances of 181–256m. The study indicated geostatistical analysis in conjunction with conventional statistical analysis could reveal spatial variability nature of soil properties and the causes behind the variability. The variability of the soil properties observed is largely due to topographic conditions and land disturbances.